Active brazing slurry and ceramic substrate metallization method
By depositing chromium and titanium sublayers on the ceramic substrate and printing brazed layers on the titanium sublayers, the problem of hollowness and low peel strength in the interface between the substrate and the copper foil during the metallization of silicon nitride ceramics is solved, and better interface connection and peel strength are achieved.
Patent Information
- Application Number
- CN202411983577.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
During the metallization process of silicon nitride ceramic AMB, there are holes in the interface between the substrate and the copper foil, and the peeling strength is low, which cannot meet the product performance requirements.
By depositing chromium and titanium sublayers on the ceramic substrate, a thin layer of interface connection between the brazing layer and the ceramic substrate is prepared by sputtering method, and a brazing layer is screen-printed on the titanium sublayer, and finally soldered in a vacuum brazing furnace.
It effectively improves the interface connection between the ceramic substrate and the copper foil, reduces the existence of voids, improves peel strength, and meets the product performance needs.
Smart Images

Figure CN119751110A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic metallization, and in particular relates to an active brazing slurry and a ceramic substrate metallization method. Background Art
[0002] Silicon nitride ceramic AMB metallization refers to the use of an active metal brazing (AMB) process on a silicon nitride (Si3N4) ceramic substrate for metallization. This process is widely used in power electronic modules, semiconductor packaging and high-performance circuit substrates. Silicon nitride ceramic AMB metallization usually screen prints active brazing slurry on a silicon nitride ceramic plate, then affixes copper sheets to both sides of the ceramic to form a copper sheet / ceramic plate / copper sheet structure, applies a certain pressure, and is placed in a vacuum brazing furnace for brazing. The disadvantage of this method is that there are inevitably voids on the interface between the substrate and the copper foil, and the low peel strength cannot meet the performance requirements of the product. Summary of the invention
[0003] The technical problem solved by the present invention is: to provide an active brazing slurry and a ceramic substrate metallization method, which solves the problem of cavities on the interface between the substrate and the copper foil and low peeling strength.
[0004] The technical solution of the present invention is: a ceramic substrate metallization method provided by the present invention is characterized by comprising:
[0005] Step 1: placing the silicon oxide ceramic substrate in anhydrous ethanol for ultrasonic cleaning to remove surface impurities, and then clamping the silicon oxide ceramic substrate on a sample holder and placing it in a sputtering chamber;
[0006] Step 2: evacuating the sputtering chamber to a vacuum and then introducing argon gas;
[0007] Step 3: applying an electric field between the cathode and the anode of the sputtering chamber, and ionizing the introduced argon gas under the action of the electric field to generate argon ions and electrons;
[0008] Step 4: adjusting the sputtering power to allow the argon ions to attack the chromium foil target under the action of a low-energy electric field, thereby depositing a chromium sublayer on the silicon oxide ceramic substrate;
[0009] Step 5: adjusting the sputtering power so that the argon ions attack the titanium foil target under the action of the high energy electric field, and depositing a titanium sublayer on the silicon oxide ceramic substrate covered with the chromium sublayer;
[0010] Step 6: screen printing a brazing layer on the silicon oxide ceramic substrate covered with the chromium sublayer and the titanium sublayer;
[0011] Step 7: Cover the two surfaces of the silicon oxide ceramic substrate with copper plates and place them in a vacuum brazing furnace for welding;
[0012] Furthermore, step 4 adjusts the sputtering power so that the argon ions attack the chromium foil target under the action of the low-energy electric field, specifically: the sputtering power is adjusted to 25-40W, and the argon gas flow rate entering the sputtering chamber is controlled to 20-50SCCM. At the same time, the silicon oxide ceramic substrate is heated to 100-120°C, and the entire sputtering process lasts 20-30 seconds.
[0013] Furthermore, step 5 adjusts the sputtering power so that the argon ions attack the titanium foil target under the action of the high-energy electric field, specifically: the sputtering power is adjusted to 50-60W, and the argon gas flow rate entering the sputtering chamber is controlled to 60-80SCCM, while the silicon oxide ceramic substrate is heated to 100-120°C, and the entire sputtering process lasts 20-30 seconds.
[0014] Furthermore, in step 5, the sputtering power is adjusted to allow argon ions to attack the titanium foil target under the action of a high-energy electric field, after a titanium sublayer is deposited on the silicon oxide ceramic substrate covered with a chromium sublayer, and before a brazing layer is screen-printed on the silicon oxide ceramic substrate covered with a chromium sublayer and a titanium sublayer in step 6, the method also includes: mixing metal powder with an adhesive to prepare a brazing material.
[0015] Furthermore, the metal powder and the adhesive are mixed to prepare the brazing material, specifically: the metal powder and the adhesive are preliminarily stirred and mixed manually, and then the mixture is placed in a high-speed disperser homogenizer and stirred for 15-45 minutes at a speed of 400-1000 rpm, and finally ground with a three-grinding machine for 2-5 times to obtain the brazing material.
[0016] Furthermore, in step 5, the sputtering power is adjusted so that the argon ions attack the titanium foil target under the action of the high-energy electric field, after the titanium sublayer is deposited on the silicon oxide ceramic substrate covered with the chromium sublayer, and before the brazing layer is screen-printed on the silicon oxide ceramic substrate covered with the chromium sublayer and the titanium sublayer in step 6, the method also includes: preparing the adhesive, the adhesive is mixed with a thickener and an organic solvent, and is placed in a water bath constant temperature magnetic stirrer for magnetic stirring, the heating temperature is 50-80°C, and the thickener is completely dissolved in the organic solvent to obtain the mixed adhesive.
[0017] Further, in step 7, the copper plates are covered on the two surfaces of the silicon oxide ceramic substrate, and placed in a vacuum brazing furnace for welding. Specifically, the copper sheets are attached to the two surfaces of the silicon oxide ceramic substrate respectively, and pressure is applied to the two surfaces, and the copper sheets are placed in a vacuum brazing furnace for brazing. The brazing temperature is set between 880°C and 980°C, and the holding time is 20-40 minutes. The vacuum degree of the vacuum brazing furnace is controlled to be better than 3×10-3Pa.
[0018] Furthermore, in step 7, after the copper plates are covered on the two surfaces of the silicon oxide ceramic substrate and placed in a vacuum brazing furnace for welding, the method further comprises:
[0019] Step 8: Take out the silicon oxide ceramic substrate after brazing, use an ultrasonic microscope to detect voids, and then put it into a 90-degree peel strength tester to test the peel strength.
[0020] The present invention also provides an active brazing slurry, which comprises the following weight percentages: 80-90% metal powder and 10-20% adhesive, wherein the metal powder comprises 55-95% copper-tin alloy powder, 0-30% silver powder, and 5-15% silicon nitride nanopowder, wherein the copper comprises 62-80% copper and 20-38% tin in the copper-tin alloy powder.
[0021] Furthermore, the weight percentage of the adhesive is: 10-20% thickener, 80-90% organic solvent, wherein the thickener is a mixture of one or more of ethyl cellulose, nitrocellulose and polyisobutylene; the organic solvent is a mixture of one or more of pinene alcohol, diethylene glycol monobutyl ether, butyl carbitol acetate and dibutyl phthalate.
[0022] The beneficial effects of the present invention are as follows: the present invention prepares a chromium sublayer and a titanium sublayer at the interface between the brazing layer and the ceramic substrate by a deposition method, wherein the chromium sublayer is sputtered on the ceramic substrate at low energy, chromium has good wettability with silicon oxide ceramics, the chromium sublayer prepared by low energy sputtering is relatively dense, and the ceramic substrate is not easily damaged during the sputtering process; the titanium sublayer is sputtered on the surface of the ceramic substrate to which the chromium sublayer is attached at high energy, and the surface roughness of the titanium sublayer prepared by high energy sputtering is relatively high, so that the adhesion between the titanium sublayer surface and the brazing material is enhanced, which is beneficial to improving the interface connection between the ceramic substrate and the copper foil. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0024] Figure 1 A flow chart of a ceramic substrate metallization method provided in this application;
[0025] Figure 2 This is a diagram of ultrasonic microscope test results in Example 1;
[0026] Figure 3 This is a diagram of ultrasonic microscope test results in Example 2;
[0027] Figure 4 This is a diagram of ultrasonic microscope test results in Example 3;
[0028] Figure 5 This is a diagram of ultrasonic microscope test results of Example 4;
[0029] Figure 6 This is a diagram of ultrasonic microscope test results in Example 5;
[0030] Figure 7 This is a diagram of ultrasonic microscope test results of Example 6;
[0031] Figure 8 This is a diagram of ultrasonic microscope test results of Example 7;
[0032] Fig. 9 This is a diagram of ultrasonic microscope test results in Example 8;
[0033] Fig.10 This is a diagram of ultrasonic microscope test results of Example 9;
[0034] Fig.11 This is a diagram of ultrasonic microscope test results in Example 10;
[0035] Fig.12 This is a diagram showing the ultrasonic microscope test results for comparative example 1;
[0036] Fig.13 This is a diagram of the ultrasonic microscope test results of comparative example 2;
[0037] Fig.14 This is a diagram showing the ultrasonic microscope test results for comparative example 1; DETAILED DESCRIPTION
[0038] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0040] The present invention provides a ceramic substrate metallization method, comprising:
[0041] Step 1: placing the silicon oxide ceramic substrate in anhydrous ethanol for ultrasonic cleaning to remove surface impurities, and then clamping the silicon oxide ceramic substrate on a sample holder and placing it in a sputtering chamber;
[0042] Step 2: evacuating the sputtering chamber to a vacuum and then introducing argon gas;
[0043] In step 2, the sputtering chamber is evacuated to a vacuum state, and then argon gas is introduced. Specifically, argon gas is filled into the sputtering chamber under high vacuum conditions (less than 3x10^-3Pa); a DC voltage is applied between the cathode (target material) and the anode to generate an electric field; and high-purity argon gas is filled to prevent the target material and the surface of the ceramic substrate from chemically reacting with oxygen or other gases in the environment, thereby ensuring the purity of the deposited layer.
[0044] In step 3, an electric field is applied between the cathode and the anode of the sputtering chamber, and the introduced argon gas is ionized under the action of the electric field to generate argon ions and electrons.
[0045] Step 4: adjusting the sputtering power to allow the argon ions to attack the chromium foil target under the action of a low-energy electric field, thereby depositing a chromium sublayer on the silicon oxide ceramic substrate.
[0046] In step 4, the sputtering power is adjusted so that the argon ions attack the chromium foil target under the action of the low-energy electric field. Specifically, the sputtering power is adjusted to 25-40W, and the argon gas flow rate entering the sputtering chamber is controlled to 20-40SCCM. At the same time, the silicon oxide ceramic substrate is heated to 100-120°C. The entire sputtering process lasts for 20-30 seconds.
[0047] Step 5: adjusting the sputtering power so that the argon ions attack the titanium foil target under the action of the high energy electric field, and depositing a titanium sublayer on the silicon oxide ceramic substrate covered with the chromium sublayer;
[0048] Step 5: Adjust the sputtering power to make the argon ions attack the titanium foil target under the action of the high-energy electric field. Specifically, adjust the sputtering power to 50-60W, and control the argon gas flow rate into the sputtering chamber to 60-80SCCM. At the same time, heat the silicon oxide ceramic substrate to 100-120°C. The whole sputtering process lasts for 20-30 seconds.
[0049] In step 4 and step 5, a thin interface connection layer (chromium sublayer + titanium sublayer) between the brazing layer and the ceramic substrate is prepared by a deposition method, and then a brazing layer is printed on the titanium sublayer and a copper foil is covered on the brazing layer to obtain an AMB ceramic copper-clad laminate. Silicon oxide ceramics have a high hardness, and combined with sputtering deposition, the hardness and wear resistance can be further enhanced.
[0050] The chromium sublayer is deposited by low-energy sputtering, and the surface of the prepared chromium sublayer is dense and smooth; the titanium sublayer is deposited by high-energy sputtering, and the surface roughness of the titanium sublayer is relatively large, and the chromium atoms and the titanium atoms are embedded in each other on the contact surface.
[0051] Low-energy sputtering is used first. On the one hand, it is to prevent the substrate from breaking. The thickness of the silicon oxide ceramic substrate is between 0.3-0.6mm, and the material is fragile. Even if it is not broken, there is a risk of hidden damage under high-energy ion impact. On the other hand, it is to prepare a film layer with higher density. Under high energy, the collision between ions is very violent, and it is difficult for chromium atoms to be stably and orderly attached to the substrate, so the density is relatively low. The chromium layer is selected because the wettability of chromium and ceramics is relatively good and the bonding ability is strong. At the same time, avoid using excessive titanium. Titanium ceramics are hard and brittle, which weakens the connection strength between ceramics and copper foil. 20-50SCCM is conducive to improving the energy density of argon ions, thereby increasing sputtering efficiency, which is suitable for processes requiring high-quality films. Excessive argon flow will increase the bombardment intensity of ions on the substrate, which may cause overheating of the substrate or surface damage. Therefore, low-energy sputtering is used during the initial attachment of the ceramic substrate.
[0052] High-energy sputtering is used in the later stage, mainly to prepare a film layer with a large surface roughness. The greater the surface roughness, the more defects and unevenness there are on the surface, which will expose more atoms or molecules. These atoms or molecules have lost some of their interactions with the surrounding atoms or molecules and are in a high-energy state, that is, the surface energy is high. The higher the surface energy, the stronger the adhesion between the titanium sublayer surface and the brazing material, which is conducive to improving the interface connection between the ceramic substrate and the copper foil and enhancing the connection strength.
[0053] Step 6, before screen printing the brazing layer on the silicon oxide ceramic substrate covered with the chromium sublayer and the titanium sublayer, also includes:
[0054] Prepare solder for printing welding layer, mix metal powder with adhesive to prepare brazing material, stir and mix metal powder and adhesive manually, wherein the metal powder ratio is 80-90%, and the adhesive ratio is 10-20%, then put the mixture into high-speed dispersing homogenizer and stir for 15-45 minutes, the speed is 400-1000 rpm, and finally grind it by three grinding machines, grinding times 2-5 times to obtain the brazing material. High metal powder content (80-90%) ensures the filling degree of metal in the brazing material, which is beneficial to the strength, thermal conductivity and electrical conductivity of the joint after welding; the adhesive content is controlled at 10-20%, which is sufficient to remove oxides and improve wettability, and can avoid corrosion problems caused by excessive adhesive residue. The speed range of 400-1000 rpm of high-speed dispersing homogenizer can provide sufficient dispersing force to make the adhesive evenly coated on the surface of metal powder, while avoiding excessive stirring to cause particle breakage or adhesive decomposition. Three-roll grinding can effectively reduce the agglomeration of metal powder particles, further optimize particle distribution, and improve the film-forming performance of the brazing material. After grinding, the rheological properties of the brazing material are better, which is convenient for screen printing or coating processes and improves construction performance.
[0055] The present invention also provides an active brazing slurry, which is composed of the following weight percentages: 80-90% metal powder and 10-20% adhesive, wherein the metal powder components are copper-tin alloy powder: 55-95%, silver powder: 0-30%, and silicon nitride nanopowder: 5-15%, wherein the copper-tin alloy powder comprises 62-80% copper and 20-38% tin.
[0056] Adding Si 3N4 nanoparticles to solder affects the performance of solder: Si 3N4 nanoparticles can hinder the growth of B-Sn grains. When Ag exists in the solder, Si 3N4 will also hinder the growth of Ag3Sn phase, making the phase particles in the brazing layer very fine. Due to grain refinement, the strength and hardness of the brazing layer are improved. Si 3N4 nanoparticles can react with Cu6Sn5 phase to form AI203 / Cu6Sn5 composite phase, which has higher hardness and strength, thereby further improving the mechanical properties of the brazing layer. The addition of Si 3N4 nanoparticles will cause the melting point of the solder to drop slightly, which helps to reduce the brazing temperature and effectively reduce the oxidation of the solder at high temperature, thereby improving the strength of the brazing layer. The titanium in the titanium sublayer has a strong adsorption capacity for the nitrogen ions in the silicon nitride powder, reacting to form TiN, which helps to achieve the wetting and connection between the solder and the silicon nitride ceramic and copper; and the Si 3N 4 nanoparticles have high surface energy, which can reduce the surface tension of the solder in the molten state, thereby improving its wettability.
[0057] The above brazing material uses copper-tin alloy powder to replace the mixture of copper powder and tin powder:
[0058] The melting point of tin powder is 232℃, the melting point of copper powder is 1083℃, and the melting point of copper-tin alloy powder is between 700-800℃. The melting point of tin powder is too low, and the brazing temperature is around 900℃. The tin powder melts too early in the reaction process, resulting in unstable reaction. The melting point and brazing temperature of copper-tin alloy powder are close to the solder, so the solder will not experience a large temperature change during the brazing process, which can reduce thermal stress; thermal stress can cause deformation of the base material, that is, reducing thermal stress can reduce deformation of the base material, reduce crack formation, and thus improve the accuracy and reliability of the brazed joint.
[0059] However, the brazing temperature is higher than the melting point of the copper-tin alloy powder: the solder melts faster, which can shorten the welding time and improve the welding efficiency. The solder melts more evenly, which reduces the formation of pores and inclusions and improves the quality of the brazed joint. In the embodiment, the metal powder contains silver, and in another embodiment, the metal powder may not contain silver: because the titanium sublayer can provide sufficient titanium, it can satisfy both the bonding between titanium and copper and the bonding between titanium and ceramics. Silver is not needed to improve the interfacial activity, and a good brazing effect can be obtained.
[0060] The adhesive is composed of a thickener and an organic solvent, wherein the thickener is one or more of ethyl cellulose, nitrocellulose, and polyisobutylene, and the organic solvent is one or more of terpineol, diethylene glycol monobutyl ether, butyl carbitol acetate, and dibutyl phthalate, wherein the thickener accounts for 10-20% and the organic solvent accounts for 80-90%. After the thickener and the solvent are weighed in proportion, they are placed in a water bath constant temperature magnetic stirrer for magnetic stirring, and the heating temperature is 50-80°C until the thickener is completely dissolved in the solvent.
[0061] Step 6: screen printing a brazing layer on the silicon oxide ceramic substrate covered with the chromium sublayer and the titanium sublayer;
[0062] Step 7: Cover the two surfaces of the silicon oxide ceramic substrate with copper plates and place them in a vacuum brazing furnace for welding;
[0063] Step 7: Cover the two surfaces of the silicon oxide ceramic substrate with the copper plate, and place it in a vacuum brazing furnace for welding. Specifically, the copper sheet is attached to the two surfaces of the silicon oxide ceramic substrate, and pressure is applied to the two surfaces. The copper sheet is placed in a vacuum brazing furnace for brazing. The brazing temperature is 880°C-980°C, and the temperature is kept at 20-40 minutes. The vacuum degree of the vacuum brazing furnace is better than 3*10-3Pa.
[0064] At a high temperature of 880℃-980℃, the brazing material completely melts and fully wets the copper sheet and the ceramic surface, achieving a strong metallurgical bond. The interface bonding between the ceramic and the metal forms a stable interface structure through the diffusion and chemical reaction of the brazing layer. Keeping the temperature for 20-40 minutes can ensure that the brazing material evenly fills the interface and eliminates possible micropores or cracks, further improving the heat resistance and mechanical properties of the bonding layer.
[0065] Step 8: Take out the silicon oxide ceramic substrate after brazing, use an ultrasonic microscope to detect voids, and then put it into a 90-degree peel strength tester to test the peel strength.
[0066] Embodiment 1
[0067] The present embodiment provides an active brazing slurry and a ceramic substrate metallization method. Before step 6, a solder for printing a welding layer is prepared. The active brazing slurry has the following proportions: the metal powder is 90% Cu70Sn30 alloy powder and 10% titanium powder; the binder is 15% ethyl cellulose and 85% diethylene glycol monobutyl ether; the ratio of metal powder to binder is 85:15.
[0068] After the thickener and the solvent are weighed in proportion, they are placed in a water bath constant temperature magnetic stirrer for magnetic stirring, heated to 70°C, and the binder is obtained after the thickener is completely dissolved. After the metal powder and the binder are weighed in proportion, they are first stirred evenly by hand, then stirred at a speed of 600 rpm for 20 minutes using a high-speed dispersing homogenizer, and finally ground three times using a three-roll grinder to obtain the active brazing slurry.
[0069] Step 6: screen printing the active brazing paste onto the silicon nitride ceramic plate.
[0070] Step 7: Stick the copper sheet on both sides of the ceramic to form a copper sheet / ceramic plate / copper sheet structure, apply a certain pressure, and put it into a vacuum brazing furnace for brazing. The brazing temperature is 930°C, the insulation time is 10 minutes, and the vacuum degree is better than 3*10-3Pa.
[0071] Step 8: Take out the brazed product, use an ultrasonic microscope to detect voids, and use a 90-degree peel strength tester to detect peel strength.
[0072] Embodiment 2
[0073] In a ceramic substrate metallization method provided in this embodiment, in step 7, copper sheets are attached to both sides of the ceramic to form a copper sheet / ceramic plate / copper sheet structure, a certain pressure is applied, and the copper sheet is placed in a vacuum brazing furnace for brazing, the brazing temperature is 930°C, the holding time is 20 minutes, and the vacuum degree is better than 3*10-3 Pa. The rest is consistent with step 1.
[0074] Embodiment 3
[0075] In a ceramic substrate metallization method provided in this embodiment, in step 7, copper sheets are attached to both sides of the ceramic to form a copper sheet / ceramic plate / copper sheet structure, a certain pressure is applied, and the structure is placed in a vacuum brazing furnace for brazing at a brazing temperature of 930° C. for a holding time of 30 minutes and a vacuum degree of better than 3*10-3 Pa. The rest is consistent with step 1.
[0076] Embodiment 4
[0077] In a ceramic substrate metallization method provided in this embodiment, in step 7, copper sheets are attached to both sides of the ceramic to form a copper sheet / ceramic plate / copper sheet structure, a certain pressure is applied, and the copper sheet is placed in a vacuum brazing furnace for brazing, the brazing temperature is 930°C, the holding time is 40 minutes, and the vacuum degree is better than 3*10-3 Pa. The rest is consistent with step 1.
[0078] Embodiment 5
[0079] In a ceramic substrate metallization method provided in this embodiment, in step 7, copper sheets are attached to both sides of the ceramic to form a copper sheet / ceramic plate / copper sheet structure, a certain pressure is applied, and the copper sheet is placed in a vacuum brazing furnace for brazing, the brazing temperature is 930°C, the holding time is 40 minutes, and the vacuum degree is better than 3*10-3 Pa. The rest is consistent with step 1.
[0080] Embodiment 6
[0081] In a ceramic substrate metallization method provided in this embodiment, in step 7, copper sheets are attached to both sides of the ceramic to form a copper sheet / ceramic plate / copper sheet structure, a certain pressure is applied, and the copper sheet is placed in a vacuum brazing furnace for brazing, the brazing temperature is 890°C, the holding time is 30 minutes, and the vacuum degree is better than 3*10-3 Pa. The rest is consistent with step 1.
[0082] Embodiment 7
[0083] In a ceramic substrate metallization method provided in this embodiment, in step 7, copper sheets are attached to both sides of the ceramic to form a copper sheet / ceramic plate / copper sheet structure, a certain pressure is applied, and the copper sheet is placed in a vacuum brazing furnace for brazing, the brazing temperature is 910°C, the holding time is 30 minutes, and the vacuum degree is better than 3*10-3 Pa. The rest is consistent with step 1.
[0084] Embodiment 8
[0085] The present embodiment provides an active brazing paste, the ratio of the solder metal powder and the binder is: the metal powder is 90% Cu70Sn30 alloy powder, 10% titanium powder; the binder is 15% ethyl cellulose, 85% diethylene glycol monobutyl ether; the ratio of the metal powder to the binder is 85:15. The rest is consistent with the sixth embodiment.
[0086] Embodiment 9
[0087] The present embodiment provides an active brazing paste, the ratio of the solder metal powder and the binder is: the metal powder is 85% Cu70Sn30 alloy powder, 15% titanium powder; the binder is 15% ethyl cellulose, 85% diethylene glycol monobutyl ether; the ratio of the metal powder to the binder is 85:15. The rest is consistent with the sixth embodiment.
[0088] Embodiment 10
[0089] The present embodiment provides an active brazing paste, the ratio of the solder metal powder and the binder is: the metal powder is 85% Cu70Sn30 alloy powder, 15% titanium powder; the binder is 15% ethyl cellulose, 85% diethylene glycol monobutyl ether; the ratio of the metal powder to the binder is 85:15. The rest is consistent with the sixth embodiment.
[0090] Comparative Example 1
[0091] Comparative Example 1
[0092] The brazing material in step 6 is Ag69Cu26.5Ti4.5 alloy slurry, and the slurry is screen-printed on a silicon nitride ceramic plate;
[0093] Step 7: Stick the copper sheet on both sides of the ceramic to form a copper sheet / ceramic plate / copper sheet structure, apply a certain pressure, and put it into a vacuum brazing furnace for brazing. The brazing temperature is 910℃, the insulation time is 30 minutes, and the vacuum degree is better than 3*10-3Pa.
[0094] Comparative Example 2
[0095] The ratio of the solder metal powder and the adhesive is: the metal powder is 63% copper powder, 27% tin powder, and 10% titanium powder; the adhesive is 15% ethyl cellulose and 85% diethylene glycol monobutyl ether; the ratio of the metal powder to the adhesive is 85:15. The rest is consistent with Example 6.
[0096] Comparative Example 3
[0097] The ratio of the metal powder and the adhesive of the solder is: the metal powder is 95% Cu70Sn30 alloy powder and 5% titanium powder; the adhesive is 15% ethyl cellulose and 85% diethylene glycol monobutyl ether; the ratio of the metal powder to the adhesive is 85:15. The rest is consistent with Example 6.
[0098] Examples 1 to 10 and Comparative Examples 1 to 3 were tested for cavitation using an ultrasonic microscope, and then put into a 90-degree peel strength tester to test the peel strength. The results are shown in the following table:
[0099]
[0100]
[0101] In Examples 1 to 7, metal powder Cu70Sn30 alloy powder 90% and titanium powder 10% were used as metal components, and the brazing temperature and time were adjusted for testing. The maximum peel strength of 13.8 N / mm was achieved at 910° C. for 30 minutes.
[0102] Examples 1 to 9 are silver-free active brazing slurries, and Comparative Example 1 is a widely used silver-copper-titanium slurry. Examples 1 to 9 can all achieve the industry standard of peel strength greater than 10N / mm, and the void results are consistent with the effects of the silver-copper-titanium slurry.
[0103] Example 6, Example 8, and Example 9 are test results when the titanium content is greater than or equal to 10%. It can be seen that the higher the titanium content, the smaller the peel strength. Comparative Example 3 is the test result when the titanium content is 5%. It can be seen that in the silver-free solder, the titanium content must be greater than 5% to obtain a good voiding effect.
[0104] Example 10 is a low-silver active brazing paste, which can achieve the industry standard of peel strength greater than 10N / mm, and the void result is consistent with that of silver-copper-titanium paste.
[0105] The metal components of the active slurry used in Example 6 and Comparative Example 2 are the same. Copper-tin alloy powder is used in Example 1, and copper powder and tin powder are used in Comparative Example 2. Obviously, the brazing effect is better after using copper-tin alloy powder.
[0106] Embodiment 11
[0107] In a ceramic substrate metallization method provided in this embodiment, in step 4, the sputtering power is adjusted to 25W, and the flow rate of argon gas entering the sputtering chamber is controlled to 30SCCM, and at the same time, the silicon oxide ceramic substrate is heated to 100-120°C, and the entire sputtering process lasts for 20 seconds. In step 5, the sputtering power is adjusted to 50W, and the flow rate of argon gas entering the sputtering chamber is controlled to 70SCCM, and at the same time, the silicon oxide ceramic substrate is heated to 100-120°C, and the entire sputtering process lasts for 20 seconds, and the rest is consistent with the first embodiment.
[0108] Embodiment 12
[0109] In a ceramic substrate metallization method provided in this embodiment, in step 4, the sputtering power is adjusted to 30 W, and the flow rate of argon gas entering the sputtering chamber is controlled to 30 SCCM, and at the same time, the silicon oxide ceramic substrate is heated to 100-120° C., and the entire sputtering process lasts for 30 seconds. In step 5, the sputtering power is adjusted to 55 W, and the flow rate of argon gas entering the sputtering chamber is controlled to 70 SCCM, and at the same time, the silicon oxide ceramic substrate is heated to 100-120° C., and the entire sputtering process lasts for 30 seconds, and the rest is consistent with the first embodiment.
[0110] Embodiment 13
[0111] In a ceramic substrate metallization method provided in this embodiment, in step 4, the sputtering power is adjusted to 35W, and the flow rate of argon gas entering the sputtering chamber is controlled to 30SCCM, and at the same time, the silicon oxide ceramic substrate is heated to 100-120°C, and the entire sputtering process lasts for 25 seconds. In step 5, the sputtering power is adjusted to 60W, and the flow rate of argon gas entering the sputtering chamber is controlled to 70SCCM, and at the same time, the silicon oxide ceramic substrate is heated to 100-120°C, and the entire sputtering process lasts for 25 seconds, and the rest is consistent with the first embodiment.
[0112] Embodiment 14
[0113] In a ceramic substrate metallization method provided in this embodiment, in step 4, the sputtering power is adjusted to 40W, and the flow rate of argon gas entering the sputtering chamber is controlled to 20SCCM, and at the same time, the silicon oxide ceramic substrate is heated to 100-120°C, and the entire sputtering process lasts for 25 seconds. In step 5, the sputtering power is adjusted to 50W, and the flow rate of argon gas entering the sputtering chamber is controlled to 60SCCM, and at the same time, the silicon oxide ceramic substrate is heated to 100-120°C, and the entire sputtering process lasts for 25 seconds, and the rest is consistent with the first embodiment.
[0114] Embodiment 15
[0115] In a ceramic substrate metallization method provided in this embodiment, in step 4, the sputtering power is adjusted to 25 W, and the flow rate of argon gas entering the sputtering chamber is controlled to 30 SCCM, and at the same time, the silicon oxide ceramic substrate is heated to 100-120° C., and the entire sputtering process lasts for 25 seconds. Step 5 of sputtering the titanium sublayer is deleted, and the rest is consistent with the first embodiment.
[0116] Embodiment 16
[0117] In a ceramic substrate metallization method provided in this embodiment, in step 4, the sputtering power is adjusted to 30W, and the flow rate of argon gas entering the sputtering chamber is controlled to 30SCCM, and at the same time, the silicon oxide ceramic substrate is heated to 100-120°C, and the entire sputtering process lasts for 25 seconds. Step 5 of sputtering the titanium sublayer is deleted, and the rest is consistent with the first embodiment.
[0118] Embodiment 17
[0119] In the ceramic substrate metallization method provided in this embodiment, the sputtering power is adjusted to 35W in step 4, and the argon gas flow rate into the sputtering chamber is controlled to 30SCCM. At the same time, the silicon oxide ceramic substrate is heated to 100-120°C, and the entire sputtering process lasts for 25 seconds. Step 5 of sputtering the titanium sublayer is deleted, and the rest is consistent with the first embodiment.
[0120] Embodiment 18
[0121] In the present embodiment, a ceramic substrate metallization method is provided. In step 4, the sputtering power is adjusted to 40W, and the flow rate of argon gas entering the sputtering chamber is controlled to 30SCCM. At the same time, the silicon oxide ceramic substrate is heated to 100-120°C, and the entire sputtering process lasts for 25 seconds. Step 5 of sputtering the titanium sublayer is deleted, and the rest is consistent with the first embodiment.
[0122] Embodiment 19
[0123] This embodiment provides a ceramic substrate metallization method, in which step 5 adjusts the sputtering power to 50 W, and controls the argon gas flow rate entering the sputtering chamber to 70 SCCM, and heats the silicon oxide ceramic substrate to 100-120°C. The entire sputtering process lasts for 25 seconds. Step 4 of sputtering the chromium sublayer is deleted, and the titanium sublayer is sputtered directly on the ceramic substrate. The rest is consistent with Example 1.
[0124] Embodiment 20
[0125] This embodiment provides a ceramic substrate metallization method, in which step 5 adjusts the sputtering power to 55 W, and controls the argon gas flow rate entering the sputtering chamber to 70 SCCM, and heats the silicon oxide ceramic substrate to 100-120°C. The entire sputtering process lasts for 25 seconds. Step 4 of sputtering the chromium sublayer is deleted, and the titanium sublayer is sputtered directly on the ceramic substrate. The rest is consistent with Example 1.
[0126] In Examples 11 to 20, an ultrasonic microscope was used to detect the voids, and then the 90-degree peel strength tester was used to test the peel strength. The results are shown in the following table:
[0127]
[0128] Note: No voids means no defects observed by the technicians with the naked eye during the experiment, while almost no voids means fewer tiny defects observed by the technicians with the naked eye. Due to the limitation of the equipment, these defects cannot be shown in the photographs. The results of this embodiment are comprehensively judged from the two dimensions of appearance and quantitative data by combining microscope observation with peel strength test.
[0129] Effect of chromium layer sputtering power, argon flow rate and time:
[0130] For the combinations of chromium layer sputtering power (25-40 W), argon gas flow rate (20-50 sccm) and time (20-30 s) of Examples 11 to 14, the peel strength ranged from 15.1 to 15.7 N / mm, and there was no void.
[0131] When the sputtering power of the chromium layer is relatively high (35 W and above) (such as Examples 13 and 14), the peeling strength is slightly lower than that of the process combination with low power (25-30 W) (such as Examples 11 and 12).
[0132] The titanium layer process conditions have a significant effect on the peel strength: Examples 11 to 14 use titanium layer sputtering
[0133] (Power 50-60W, Ar flow 60-80sccm, time 20-30s), the peel strength is relatively high (>15N / mm). In Examples 15 to 18, no titanium layer sputtering was used, and the peel strength was significantly reduced to 12.0-13.5N / mm, indicating that the presence of the titanium layer significantly improved the interface bonding performance.
[0134] When only the titanium layer is sputtered (power 50-55 W, argon flow rate 70 sccm, time 25 s), the peel strength is further reduced to 11.5-11.7 N / mm, slightly higher than the part without titanium layer (Examples 15-18), but much lower than the examples using both chromium layer and titanium layer (Examples 11-14).
[0135] The above embodiments only express the preferred implementation modes of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A ceramic substrate metallization method, characterized in that: include: Step 1: placing the silicon oxide ceramic substrate in anhydrous ethanol for ultrasonic cleaning to remove surface impurities, and then clamping the silicon oxide ceramic substrate on a sample holder and placing it in a sputtering chamber; Step 2: evacuating the sputtering chamber to a vacuum and then introducing argon gas; Step 3: applying an electric field between the cathode and the anode of the sputtering chamber, and ionizing the introduced argon gas under the action of the electric field to generate argon ions and electrons; Step 4: adjusting the sputtering power to allow the argon ions to attack the chromium foil target under the action of a low-energy electric field, thereby depositing a chromium sublayer on the silicon oxide ceramic substrate; Step 5: adjusting the sputtering power so that the argon ions attack the titanium foil target under the action of the high energy electric field, and depositing a titanium sublayer on the silicon oxide ceramic substrate covered with the chromium sublayer; Step 6: screen printing a brazing layer on the silicon oxide ceramic substrate covered with the chromium sublayer and the titanium sublayer; Step 7: Cover the two surfaces of the silicon oxide ceramic substrate with copper plates and place them in a vacuum brazing furnace for welding.
2. A ceramic substrate metallization method as claimed in claim 1, characterized in that: Step 4: Adjust the sputtering power to make the argon ions attack the chromium foil target under the action of the low-energy electric field. Specifically, adjust the sputtering power to 25-40W, and control the argon gas flow rate into the sputtering chamber to 20-50SCCM. At the same time, heat the silicon oxide ceramic substrate to 100-120°C. The whole sputtering process lasts for 20-30 seconds.
3. A ceramic substrate metallization method as claimed in claim 2, characterized in that: Step 5: Adjust the sputtering power to make the argon ions attack the titanium foil target under the action of the high-energy electric field. Specifically, adjust the sputtering power to 50-60W, and control the argon gas flow rate into the sputtering chamber to 60-80SCCM. At the same time, heat the silicon oxide ceramic substrate to 100-120°C. The whole sputtering process lasts for 20-30 seconds.
4. A ceramic substrate metallization method according to claim 1, characterized in that: In step 5, the sputtering power is adjusted to allow argon ions to attack the titanium foil target under the action of a high-energy electric field, after a titanium sublayer is deposited on the silicon oxide ceramic substrate covered with a chromium sublayer, and before a brazing layer is screen-printed on the silicon oxide ceramic substrate covered with the chromium sublayer and the titanium sublayer in step 6, the method also includes: mixing metal powder with an adhesive to prepare a brazing material.
5. A ceramic substrate metallization method as claimed in claim 4, characterized in that: The method of preparing the brazing material by mixing the metal powder with the adhesive is as follows: the metal powder and the adhesive are preliminarily stirred and mixed manually, and then the mixture is placed in a high-speed dispersing homogenizer and stirred for 15-45 minutes at a speed of 400-1000 rpm, and finally ground with a three-grinding machine for 2-5 times to obtain the brazing material.
6. A ceramic substrate metallization method as claimed in claim 5, characterized in that: In step 5, the sputtering power is adjusted to allow argon ions to attack the titanium foil target under the action of a high-energy electric field, after a titanium sublayer is deposited on the silicon oxide ceramic substrate covered with a chromium sublayer, and before a brazing layer is screen-printed on the silicon oxide ceramic substrate covered with the chromium sublayer and the titanium sublayer in step 6, the method further includes: preparing the adhesive, mixing the adhesive with a thickener and an organic solvent, placing the adhesive in a water bath constant temperature magnetic stirrer for magnetic stirring, heating the adhesive at a temperature of 50-80°C, and waiting for the thickener to be completely dissolved in the organic solvent to obtain the mixed adhesive.
7. A ceramic substrate metallization method as claimed in claim 1, characterized in that: Step 7: Cover the two surfaces of the silicon oxide ceramic substrate with copper plates, and place them in a vacuum brazing furnace for welding. Specifically, the copper plates are respectively attached to the two surfaces of the silicon oxide ceramic substrate, and pressure is applied to the two surfaces, and the plates are placed in a vacuum brazing furnace for brazing. The brazing temperature is set between 880°C and 980°C, and the insulation time is 20-40 minutes. The vacuum degree of the vacuum brazing furnace is controlled to be better than 3×10-3Pa.
8. A ceramic substrate metallization method according to claim 1, characterized in that: After the copper plates are covered on the two surfaces of the silicon oxide ceramic substrate in step 7 and placed in a vacuum brazing furnace for welding, the method further comprises: Step 8: Take out the silicon oxide ceramic substrate after brazing, use an ultrasonic microscope to detect voids, and then put it into a 90-degree peel strength tester to test the peel strength.
9. An active brazing slurry, characterized in that: The active brazing slurry is composed of 80-90% metal powder and 10-20% adhesive, wherein the metal powder comprises 55-95% copper-tin alloy powder, 0-30% silver powder and 5-15% silicon nitride nanopowder, wherein copper comprises 62-80% copper and 20-38% tin in the copper-tin alloy powder.
10. An active brazing slurry according to claim 9, characterized in that: The weight percentages of the adhesive are as follows: the thickener accounts for 10-20%, and the organic solvent accounts for 80-90%, wherein the thickener is a mixture of one or more of ethyl cellulose, nitrocellulose and polyisobutylene; and the organic solvent is a mixture of one or more of pinene alcohol, diethylene glycol monobutyl ether, butyl carbitol acetate and dibutyl phthalate.